2011
DOI: 10.1002/cyto.a.21073
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stromal cells express CD14 cross‐reactive epitopes

Abstract: Mesenchymal stromal cells (MSCs) do not express a unique definite epitope or marker gene. As such, minimal criteria were recently established for defining multipotent MSC. These criteria include expression of CD73, CD90, CD105, and a lack of hematopoietic marker expression. However, we detected binding of a CD14 antibody on bone marrowand placenta-derived MSC and investigated the staining of CD14 antibodies on these MSC in more detail. The MSC were isolated from human bone marrow and placenta tissue, expanded,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 44 publications
3
37
0
Order By: Relevance
“…However, we did not observe any differences between the plain MSCs cultured in OB-medium, or OB-medium supplemented with VEGF, indicating that the mechanism requires the presence of cells from the MNCfraction, such as CD34+ or CD14+ cells. MSCs have indeed been described to have a CD14-crossreactive epitope [24] demonstrating a cell-cell contact dependent interaction mechanism.…”
Section: Discussionmentioning
confidence: 98%
“…However, we did not observe any differences between the plain MSCs cultured in OB-medium, or OB-medium supplemented with VEGF, indicating that the mechanism requires the presence of cells from the MNCfraction, such as CD34+ or CD14+ cells. MSCs have indeed been described to have a CD14-crossreactive epitope [24] demonstrating a cell-cell contact dependent interaction mechanism.…”
Section: Discussionmentioning
confidence: 98%
“…Expression of cell surface antigens on MSC was explored by flow cytometry as described recently [6]. The cells were detached by mild proteolysis (Accutase, Sigma-Aldrich), counted by aid of a hematocytometer and 2x10 5 The samples were analyzed by flow cytometry (LSRII, BD Biosciences).…”
Section: Flow Cytometry and Cell Sortsmentioning
confidence: 99%
“…They express a variety of cell surface antigens, including CD29, CD73, CD90, CD140b, CD105, CD146 and CD166, but lack expression of antigens characteristic for hematopoietic or endothelial cells such as CD11b, CD14, CD34, CD31, CD45, or CD133 [3][4][5][6][7][8]. Widely used protocols for preparation of MSC from bone marrow (bmMSC) start with a crude mix of cells and debris in suspension.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, we should consider that some epitopes of antigens may have a cross reaction with doubtful antibodies. For example, it was reported that human mesenchymal stromal cells expressed CD14 cross-reactive epitopes depending on the clone of antibody [50].…”
Section: /Cd206mentioning
confidence: 99%